High thermal stability of energy storage density and large strain improvement of lead-free Bi0.5(Na0.40K0.10)TiO3piezoelectric ceramics doped with La and Zr - Pichitchai Butnoi (2018)
© 2018 Elsevier Ltd Properties of lead-free Bi0.5-xLaxNa0.40K0.10Ti0.98Zr0.02O3(x = 0.000–0.040) ceramics were investigated. All ceramics have a pure perovskite structure. A high energy storage density (∼1.00 J/cm3) at room temperature (RT) is noted for the x = 0.030 sample, while x = 0.020 and 0.040 samples have very high thermal stability of energy storage density of ∼3% (at 75–150 °C). Furthermore, the x = 0.030 and 0.040 samples have the highest energy storage efficiency (η) value of 94% at 125 °C with high thermal stability (η = 84–95% at 25–150 °C). The x = 0.005 sample has high electric field-induced strain (Smax= 0.42%) and high normalized strain coefficient (d*33= Smax/Emax= 700 pm/V) with large improvements (∼200% and 163% for Smaxand d*33, respectively), as compared to the based composition. This ceramic system has potentials for piezoelectric and/or energy storage density applications.